New species of the caddisfly genus Alterosa Blahnik 2005 (Trichoptera: Philopotamidae: Philopotaminae) from Brazil - Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2013)
Alterosa Blahnik 2005 contains 23 described species distributed in southern and southeastern Brazil. Twelve new species in the caddisfly genus Alterosa are described from Brazil: Alterosa affinis sp. nov., A. bandeira sp. nov., A. bilanceolata sp. nov., A. caissara sp. nov., A. capixaba sp. nov., A. catarinae sp. nov., A. graciosa sp. nov., A. inappendiculata sp. nov., A. morato sp. nov., A. paranaensis sp. nov., A. ruschii sp. nov., and A. spiesae sp. nov. Illustrations of the male genitalia, descriptions, and diagnosis are provided for each of the new species. In addition, new distribution records in Brazilian states are given for A. caparaonensis, A. flinti, A. intervales and A. marinonii.